Design and documentation as attributes to waste generation at construction sites. Issue 1 (1st March 2023) - Moeis, A A A; Che Ahmad, A; Tharim, A H A; Othman, N
Abstract: Rapid demand of housing and infrastructure development in Malaysia had result in more construction and consequently increase the construction waste. Construction waste takes major impact to the environmental if there is no proper management of construction waste from earliest point of waste generated until waste disposal. Thus, it is important to identify attributes influencing construction waste generated at construction sites. This study aims to determine design and documentation as attributes of construction waste generation. This study was conducted at Putrajaya, Malaysia. Putrajaya was selected because this city is pioneer in urban development in measuring and promoting green development activities in Malaysia. Quantitative study using questionnaire survey was conducted at construction sites in Putrajaya. A total of 21 respondents from the construction sites have returned the survey. Using relative importance index (RII) as the analysis tools, this study determined that the design and documentation are waste generation attributes at construction sites. Findings of this study could assist more comprehensive study in determining the attributes of waste generation at construction sites.